Mechanisms underpinning successful decision making in skilled youth soccer players: An analysis of visual search behaviors - Vaeyens, R.; Lenoir, M.; Williams, A. M.; Philippaerts, R. M. (Journal of Motor Behavior, 2007)
The authors examined the complex interactions between perception, cognition, and expertise by using a film-based decision-making test. They stratified 40 youth soccer players (aged 13.0-15.8 years) into groups by using a within-task criterion. They assigned the players to successful or less successful groups on the basis of their performance on a laboratory-based test of tactical skill. Using soccer-specific film simulations, movement-based response measures, and eye movement registration techniques, the authors determined the players' decision-making processes and skill level. The results showed that investigators can use film-based tests to discriminate soccer players of comparable experience and playing level on the basis of their decision-making skills. When compared with their less successful counterparts, successful decision-makers used more goal-oriented search strategies, which resulted in superior performance, as characterized by faster decision times and greater response accuracy. Successful decision-makers (a) spent more time fixating the player in possession of the ball and (b) alternated gaze more frequently between that player and other areas of the display. An earlier study in which researchers (R. Vaeyens, M. Lenoir, A. M. Williams, L. Mazyn, & R. M. Philippaerts, 2007) stratified participants into groups on the basis of playing level had not revealed those differences. The implication of the present findings is that a withintask criterion provides investigators with a more sensitive approach when they try to identify the mechanisms underlying decision-making skill. Implications for research and practice are discussed.